Program Intervensi Berbasis Masyarakat BNN pada Penyalahgunaan Narkoba di Kelurahan Cawang Jakarta Timur - Suci, Melati Aulia; Salim, Luthfi; Rosana, Ellya (CIC Lembaga Riset dan Konsultan Sosial, 2024)
This study aims to identify the issues and causes of drug abuse through a community-based intervention program. The research employs a qualitative, descriptive approach. Informants were selected using a purposive sampling technique, targeting the administrators of Cawang Subdistrict, East Jakarta, as program implementers, and the National Narcotics Agency (BNN) as the government institution responsible for overseeing program execution in the field. The findings indicate that the community-based intervention program in Cawang Subdistrict addresses drug abuse through a series of activities, each with its own specific function, implemented progressively and continuously. There are six key implementation programs: socialization, mapping, outreach, early assessment, rehabilitation recommendations, and monitoring and recovery.